An overview of less commonly taught languages education in China: historical perspectives and practical concerns - Wu, Jiewei (Onomázein, 2021)
The teaching of less commonly taught languages (LCTLs) in China started in late World War II and developed rapidly after the implementation of China’s reform and opening-up policy. In the 21st century, LCTLs education has entered a new stage. The Chinese government has promulgated a good number of policies to encourage the development of LCTLs professionals. In the meantime, the changing international landscape and the adjustment of the national development strategies have raised higher requirements and expectations for the construction of LCTLs majors. With an overview of the history of LCTLs undergraduate education, this paper focuses on the process of LCTLs undergraduate professionals development in China in the 21st century as well as summarizes the achievements and challenges of Chinese LCTLs education from the perspectives of disciplinary planning, curriculum development, teacher development, international training, and artificial intelligence.